1987
DOI: 10.1111/j.1530-0277.1987.tb01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine, Psychophysiological and Subjective Reactivity to an Alcohol Placebo in Male Alcoholic Patients

Abstract: Alteration in neuroendocrine activity associated with the regulation of energy metabolism and food intake may play a role in characterizing the alcohol dependent state. Alcoholics, when compared to controls, demonstrated significantly larger and more rapid glucose and insulin responses following the consumption of a placebo beer, which they believed contained alcohol. The existence of significant correlations between peak neuroendocrine responses and desire to drink, anxiety, as well as psychophysiological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Such observed responses are also inconsistent with a model of CAntRs to ARCs (described above) since alcohol has been consistently shown to have the unconditioned effects of tachycaria (Docter & Perkins, 1960;Docter et al, 1966;Holmberg & Martens, 1955;Mendelson & LaDou, 1984) and increased skin conductance (Carpenter, 1957;Greenberg & Carpenter;Levenson et al, 1980). Two studies have found a peripheral hypothermic response to CE (Laberg, 1986;Dolinsky, 1987) and two have found no measurable change (Kaplan et al, 1983;Corty et al, 1988), although the latter study found that temperature was affected by the order of presentation of neutral and alcoholic stimuli in alcoholics. Again this would appear antithetic to a CAntR model where conditioned hyperthermia is predicted (Crowell et al, 1981;Le et al, 1979;Mansfield & Cunningham, 1980).…”
Section: Crs To Arcs In Alcohol-dependent and Social Drinkersmentioning
confidence: 91%
See 3 more Smart Citations
“…Such observed responses are also inconsistent with a model of CAntRs to ARCs (described above) since alcohol has been consistently shown to have the unconditioned effects of tachycaria (Docter & Perkins, 1960;Docter et al, 1966;Holmberg & Martens, 1955;Mendelson & LaDou, 1984) and increased skin conductance (Carpenter, 1957;Greenberg & Carpenter;Levenson et al, 1980). Two studies have found a peripheral hypothermic response to CE (Laberg, 1986;Dolinsky, 1987) and two have found no measurable change (Kaplan et al, 1983;Corty et al, 1988), although the latter study found that temperature was affected by the order of presentation of neutral and alcoholic stimuli in alcoholics. Again this would appear antithetic to a CAntR model where conditioned hyperthermia is predicted (Crowell et al, 1981;Le et al, 1979;Mansfield & Cunningham, 1980).…”
Section: Crs To Arcs In Alcohol-dependent and Social Drinkersmentioning
confidence: 91%
“…Other responses to ARCs which have been reported include raised serum insulin and glucose and decreased cortisol (Dolinsky et al, 1987) the significance of which is at present unclear. One early study found pupillary dilation in response to the smell of a favourite alcoholic drink in alcoholics (Kennedy, 1971).…”
Section: Crs To Arcs In Alcohol-dependent and Social Drinkersmentioning
confidence: 97%
See 2 more Smart Citations
“…As acute alcohol consumption triggers cortisol release, it is possible that conditioning results in an appetitive response to cues which also includes cortisol release and which may be involved in motivation to drink. However, depressed cortisol plasma levels at baseline, throughout alcohol cue exposure, and during consumption of alcohol have also been observed in inpatient alcoholics relative to controls (Dolinsky et al., 1987). The mixed findings from research investigating the relationship between cortisol function and alcohol cues, suggests a dysfunctional HPA system rather than specific cortisol hyporesponsivity.…”
Section: The Role Of Cortisol In Motivation To Drinkmentioning
confidence: 99%